Subjective verbal predicate of state and its distributive characteristics (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article analyzes the distributional characteristics within subjective verbal predicates of internal and external state and determines basic model types of sentences that form these kinds of predicates. This paper also identifies the verbs valence features organizing the sentence centers with the state semantics. It is noted that the system search in the structural language organization and attempts to represent the syntactic notions not only through their structural, but also by means of their propositional and semantic features stimulate linguistics development. This research confirms the idea that formalized expressions of a sentence structure (sentence block / model) allow to spread, expand and define the outlines of “external” and “internal” circulating. Moreover correlation of formal and content aspects in a sentence can be clearly defined. Besides this approach opens new perspectives in the study of word stock and syntax interrelation, including the lexical units that fill a sentence model / block organizing semantic structure of the sentence.Furthermore this paper emphasizes that the leading role in the organizing syntactic structure and optimal representing of the predicate syntagmatic potential belongs to its meaning. Language investigation demonstrates that each syntactic structure formation mostly depends on two basic notions such as the semantic structure of words illustrating a predicate and the manifestation of its components in a certain distributive word setting. The results of this research draw to conclusion that the implementation of model semantics in sentence with verbal predicates depends on the way of expressing the subjective syntactic unit. This article also outlines the basic forms of a subject in the sentence structure.
Keywords: verbal predicate; state; subjective syntactic unit; internal state; external state